Bali Cattle Cultivation and Eco-Tourism in Ayunan Village Abiansemal District, Badung - Astiti, Ni Made Ayu Gemuh Rasa; Astara, I Wayan Wesna; Eryani, I Gusti Agung Putu (Civil and Environmental Science Journal (CIVENSE), 2021)
Ayunan Village, is located in Abiansemal sub-district, Badung regency, Bali. Bali cattle are germplasm that must be preserved, for that we are collaborating with the Bali Karang Ayu and Karya laksana cattle groups in Ayunan village. The maintenance of Bali cattle in partners is very constrained by capital, feed and management of Balinese cattle maintenance is not carried out professionally because it is managed in a family, traditional way and is not a main source of livelihood. Bali cattle maintenance is only a sideline to fill spare time on the sidelines of farming time. The management of cow dung and manure has not been managed properly, which should still be managed into organic fertilizer, sold to farmers so that it can increase the income of farmers, so the solution we offer is to provide assistance and consultation as well as demonstration plots regarding good and correct management of Balinese cattle rearing. to increase Bali cattle production. The results of this community service activity can increase production, productivity as well as produce organic fertilizer from cow dung that can be sold so as to increase the income of Balinese cattle farmers in the two Bali cattle groups that we partner with.